2016
DOI: 10.1111/tri.12861
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of exhaled nitric oxide and aerobic capacity for sepsis complications after liver transplantation

Abstract: Our objective was to investigate the predictive value of fractional nitric oxide (NO) concentration in exhaled breath (FeNO) and aerobic capacity (peak VO ) for postoperative sepsis in liver transplantation candidates. Patients were identified and charts of all consecutive patients were prospectively reviewed. Bacterial sepsis represented the commonest postoperative complications (30%), which was attributed to peritonitis, pneumonia, and catheter-related infections. Preoperative FeNO and peak VO values were lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Many factors have been proposed as potential predictors of LT-related sepsis, including exhaled nitric oxide, aerobic capacity, plasma amino acid profile, and muscle wasting [ 8 10 ]. However, most of these risk factors concern only the postoperative period, and the value of these reports has been limited by the lack of a clear definition of postoperative sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been proposed as potential predictors of LT-related sepsis, including exhaled nitric oxide, aerobic capacity, plasma amino acid profile, and muscle wasting [ 8 10 ]. However, most of these risk factors concern only the postoperative period, and the value of these reports has been limited by the lack of a clear definition of postoperative sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have already found an association between CRF, expressed as VO 2 peak, and immunological status or risk of infections in other study populations [17-19, 27, 28]. In patients awaiting liver transplantation, low CRF has been found to be a significant predictor for infectious and septic perioperative events [16, 17]; even other infections, such as periodontitis has been associated with poor CRF [27]. In patients with ESKD, however, no data regarding a possible correlation between poor CRF and infectious events has yet been published [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…CRF has already been associated with the risk of infectious events in some populations [16, 17]. Previous studies demonstrated that VO 2 peak directly correlated with the proportion of CD4+ naive T-cells, leading to a favorable immunological environment through the prevention of the age-associated decline in immune function (immunosenescence) [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, several potential predictors of sepsis in the posttransplant period have been described: muscle wasting, nitric oxide, aerobic capacity, and plasma amino acid profile. [27][28][29] Candel et al showed that age (>50 years), nosocomial infections, and lung infections are predictors of septic shock in SOT recipients. 30 But each allograft has specific pathophysiologic predictors of sepsis and outcomes.…”
Section: Predictors Of Transplant-related Sepsis and Sepsis-related Outcomesmentioning
confidence: 99%